New video on rattan - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
video on rattan IDRC - Communication Division PO Box 8500 - Ottawa - Ontario CANADA K1G 3H9